Combined cardiac surgery in a Marfan syndrome patient with severe scoliosis via lower hemisternotomy: a case report - Shun-Ichiro Sakamoto; Ryosuke Amitani; Yusuke Motoji; Takako Yamaguchi; Atsushi Hiromoto; Kenji Suzuki; Yosuke Ishii (Surgical Case Reports, 2022)
Abstract Background Scoliosis is one of the symptoms manifested by patients with Marfan syndrome (MFS). Deformity of the thoracic cavity due to severe scoliosis may cause difficulty during cardiac surgery in terms of the surgical approach and instrument manipulation; however, only a few reports have been available regarding the surgical case of MFS with severe scoliosis. Here, we report a case of combined aortic valve replacement and left atrial appendage closure in a patient with MFS who had severe scoliosis using lower hemisternotomy. Case presentation A 62-year-old female with MFS was referred to our hospital after being diagnosed with severe aortic regurgitation and paroxysmal atrial fibrillation with a history of cerebral thromboembolism. The aortic valve showed severe insufficiency due to cusp prolapse, whereas the aortic root was moderately dilated (42 mm). Echocardiography revealed severe regurgitation with reduced left ventricular ejection function (32%) and massive left ventricular diastolic dimension (88 mm). Moreover, combined aortic valve replacement and left atrial appendage closure was indicated. However, the patient had chest deformity due to severe scoliosis. Thus, conventional full sternotomy or thoracotomy was considered an inappropriate surgical approach. Lower hemisternotomy was selected on the basis of three-dimensional reconstruction imaging of the aorta, left atrial appendage, sternum, and rib. Sternal elevation and rib retraction with the costal arch folded back provided enough surgical field for the combined procedures to be safely conducted. The postoperative course was uneventful, except for predicted prolonged mechanical ventilation with the assistance of intraaortic balloon pumping. Thereafter, the patient has been free from any cardiac and cerebrovascular event. Conclusions Lower hemisternotomy can be useful for combined cardiac surgery in MFS with severe scoliosis.